(untitled) (Journal of Enam Medical College, 2017)
The World Association of Medical Journal Editors (WAME) Board has recently announced the publication of the WAME statement on Identifying Predatory or Pseudo-Journals (posted on February 18, 2017). Members of WAME are permitted to republish the statement in their journals. As Editor-in-Chief and Editor of Journal of Enam Medical College are members of WAME, we are republishing this important paper in Journal of Enam Medical College. J Enam Med Col 2017; 7(2): 62-68